تفسیر احسن التفاسیر میں جمع و تدوین قرآن کی اصولی و کلامی مباحث کا تجزیاتی مطالعہ - Adnan Roshan; Muhammad Hammad Lakhvi (الآفاق اسلامی و تحقیقی مجلہ, 2022)
Syed Ahmad Hassan is a renowned Exegete of the 20th century.His Tafseer “Ahsan-ul-Tafaseer” enjoys very prominent place among the Tafseeri literature of sub-continent, The Holy Quran alone has the characteristic that it will remain in its original state till the Day of Judgment. Allah Almighty Himself has taken the responsibility of protecting it. He instructed at one place: That is, we have revealed the Quran and we will protect it. Not only words but Allah Almighty Himself has been taken the responsibility of interpreting the meanings. The revelation of the Quran was done little by little as required. Sometimes one verse and sometimes a few verses keep coming down. The order of descent was completely different from the current order. This series spanned the entire era of the Prophet (PBUH). Therefore, it was difficult, if not impossible, to come before the Prophet (PBUH) in book form like today.